Epigenetic Effects of PTSD Remediation in Veterans Using Clinical Emotional Freedom Techniques: A Randomized Controlled Pilot Study. Issue 1 (January 2018) - Church, Dawson; Yount, Garret; Rachlin, Kenneth; Fox, Louis; Nelms, Jerrod
Purpose: To assess the feasibility of measuring changes in gene expression associated with post-traumatic stress disorder (PTSD) treatment using emotional freedom techniques (EFT). Design: Participants were randomized into an EFT group receiving EFT and treatment as usual (TAU) throughout a 10-week intervention period and a group receiving only TAU during the intervention period and then receiving EFT. Setting: A community clinic and a research institute in California. Participants: Sixteen veterans with clinical levels of PTSD symptoms. Intervention: Ten hour-long sessions of EFT. Measures: Messenger RNA levels for a focused panel of 93 genes related to PTSD. The Symptom Assessment 45 questionnaire, Hospital Anxiety and Depression Scale, Insomnia Severity Scale, SF-12v2 for physical impairments, and Rivermead Postconcussion Symptoms Questionnaire. Analysis: Pre-, posttreatment, and follow-up mean scores on questionnaires were assessed using repeated measures 1-way analysis of variance. A Student t test and post hoc analyses were performed on gene expression data. Results: Post-traumatic stress disorder symptoms declined significantly in the EFT group (−53%, P < .0001). Participants maintained their gains on follow-up. Significant differential expression of 6 genes was found ( P < .05) when comparing the expression levels before and after the intervention period in participants receiving EFT. Conclusion: Study results identify candidate gene expression correlates of successful PTSD treatment, providing guidelines for the design of further studies aimed at exploring the epigenetic effects of EFT.